Design of SnO2@Air@TiO2 hierarchical urchin-like double-hollow nanospheres for high performance dye-sensitized solar cells. (1st September 2019) - Wang, Yinglin; Ma, Chao; Wang, Chen; Cheng, Pengfei; Xu, Luping; Lv, Li; Zhang, Hua
Highlights: SnO2 @Air@TiO2  hierarchical double-hollow nanospheres have been fabricated. This double-hollow structure is an excellent carrier for dye molecules. This composite structure increased the transmission of photogenerated electrons. Abstract: The hierarchical double-hollow SnO2 @Air@TiO2 microspheres (SATS) have been successfully synthesized by coating of SiO2 and TiO2 on the SnO2 templates layer by layer, and its detailed performances for dye-sensitized solar cells (DSSCs) application also have been studied. SATS microspheres have an average diameter of about 600 nm while the sizes of SnO2 hollow spheres are about 250 nm. The urchin-like SnO2 /TiO2 composite microspheres with a large specific surface area of 96.1 m 2 /g promote dye adsorption and efficient electron transport so as to increase short-circuit photocurrent density to 13.69 mA/cm 2 . Compared to the traditional simple hollow structure, the double-hollow structure can ulteriorly improve light scattering ability. Hence, it reveals that the DSSC made from SATS nanospheres and P25 exhibits a higher photo conversion efficiency of 6.77%, a 33% improvement compared to the DSSC made from pure P25. The results indicate that the improved photovoltaic performance of SATS DSSCs can mainly attribute to the unique urchin-like double-hollow microstructure and the synergistic effect of SnO2 /TiO2 composite material.